Pulmonary vascular resistance and clinical outcomes in patients with pulmonary hypertension: a retrospective cohort study. Issue 9 (September 2020) - Maron, Bradley A; Brittain, Evan L; Hess, Edward; Waldo, Stephen W; Barón, Anna E; Huang, Shi; Goldstein, Ronald H; Assad, Tufik; Wertheim, Bradley M; Alba, George A; Leopold, Jane A; Olschewski, Horst; et al.
Summary: Background: In pulmonary hypertension subgroups, elevated pulmonary vascular resistance (PVR) of 3·0 Wood units or more is associated with poor prognosis. However, the spectrum of PVR risk in pulmonary hypertension is not known. To address this area of uncertainty, we aimed to analyse the relationship between PVR and adverse clinical outcomes in pulmonary hypertension. Methods: We did a retrospective cohort study of all patients undergoing right heart catheterisation (RHC) in the US Veterans Affairs health-care system (Oct 1, 2007–Sep 30, 2016). Patients were included in the analyses if data from a complete RHC and at least 1 year of follow-up were available. Both inpatients and outpatients were included, but individuals with missing mean pulmonary artery pressure (mPAP), pulmonary artery wedge pressure, or cardiac output were excluded. The primary outcome measure was time to all-cause mortality assessed by the Veteran Affairs vital status file. Cox proportional hazards models were used to assess the association between PVR and outcomes, and the mortality hazard ratio was validated in a RHC cohort from Vanderbilt University Medical Center (Sept 24, 1998–June 1, 2016). Findings: The primary cohort (N=40 082; 38 751 [96·7%] male; median age 66·5 years [IQR 61·1–73·5]; median follow-up 1153 days [IQR 570–1971]), included patients with a history of heart failure (23 201 [57·9%]) and chronic obstructive pulmonary disease (13 348 [33·3%]). We focused on patients at risk for pulmonary hypertension based on a mPAP of at least 19 mm Hg (32 725 [81·6%] of 40 082). When modelled as a continuous variable, the all-cause mortality hazard for PVR was increased at around 2·2 Wood units compared with PVR of 1·0 Wood unit. Among patients with a mPAP of at least 19 mm Hg and pulmonary artery wedge pressure of 15 mm Hg or less, the adjusted hazard ratio (HR) for mortality was 1·71 (95% CI 1·59–1·84; p<0·0001) and for heart failure hospitalisation was 1·27 (1·13–1·43; p=0·0001), when comparing PVR of 2·2 Wood units or more to less than 2·2 Wood units. The validation cohort (N=3699, 1860 [50·3%] male, median age 60·4 years [49·5–69·2]; median follow-up 1752 days [IQR 1281–2999]) included 2870 patients [77·6%] with mPAP of at least 19 mm Hg (1418 [49·4%] male). The adjusted mortality HR for patients in the mPAP of 19 mm Hg or more group and with PVR of 2·2 Wood units or more and pulmonary artery wedge pressure of 15 mm or less Hg (1221 [42·5%] of 2870) was 1·81 (95% CI 1·33–2·47; p=0·0002). Interpretation: These data widen the continuum of clinical risk for mortality and heart failure in patients referred for RHC with elevated pulmonary artery pressure to include PVR of around 2.2 Wood units and higher. Testing the generalisability of these findings in at-risk populations with fewer cardiopulmonary comorbidities is warranted. Funding: None.